(untitled) (Global Journal of Human-Social Science, 2022)
The study investigated individual, and joint contribution effect of family cohesion, distress disclosure, retirement adjustment, and social support to the mental health status of retirees in Ondo State. Survey research design was used in the study. The population comprises all teacher retirees from the public primary and secondary schools in the State. A sample of n = 115 was purposively drawn from retirees in two Local Government Areas in the State. Two hypotheses guided the study. The results showed that family cohesion has a positive significant effect (Beta weight = 0.621, R 2 =0.386, F-value = 71.636, p-value = 0.000< 0.05), while distress disclosure has a negative significant effect (Beta weight = -0.221, R 2 =0.049, F-value = 5.86, p-value = 0.017< 0.05) on the mental health status of the retirees. Further results showed that retirement adjustment has a positive significant effect (Beta weight = 0.418, R 2 =0.175, F-value = 24.126, p-value = 0.000< 0.05) while social support has a non-significant effect (Beta weight = 0.022, R 2 =0.000, F-value = 0.054, p-value = 0.817> 0.05) on the mental health status of the respondents.